Tribocorrosion behavior of Ti–C–O–N nanostructured thin films (black) for decorative applications - Lima, P. (2013)
In the past few years, tribocorrosion has become a focus of research because of its relevance in terms of the future in-service degradation mechanisms of materials. In the particular case of decorative coatings, tribocorrosion is certainly one of the most important issues, and sweat corrosion and human contact wear are two other factors that may act as material selection tools. Thus, the current study aimed to investigate the tribocorrosion behavior of a new class of thin films, the Ti–C–O–N system, which is being developed to be used as a surface decorative material due to its relatively dark appearance. The films were prepared by reactive magnetron sputtering. The influence of the structural features on the tribocorrosion behavior is discussed.